Review of Advancements in Coal Geology - Vishwakarma, Chaitali (Journal of Advanced Research in Geo Sciences & Remote Sensing; Vol 11 No 1&2 (2024): Journal of Advanced Research in Geo Sciences & Remote Sensing, 2024)
Coal geology is a critical field within the earth sciences, focusing on the study of coal formation, composition, structure, and the processes that lead to its economic extraction and utilization. Recent advances in this field have expanded our understanding of coal’s geological history, environmental impacts, and potential future uses. This review highlights significant developments in coal geology, including advancements in the characterization of coal seams, understanding of coal formation environments, and innovative approaches to coal utilization and environmental management. Key topics covered include geochemical and petrographic analysis techniques, the role of paleoenvironments and tectonic settings in coal formation, and the development of clean coal technologies and alternative uses for coal. By integrating these new insights, the field of coal geology continues to evolve, supporting more efficient and environmentally sustainable practices in the coal industry. The review aims to provide a comprehensive overview of current research trends and future directions in coal geology, emphasizing the importance of interdisciplinary approaches in addressing the complex challenges associated with coal resources.